LITERATURE REVIEW : Hubungan Koordinasi Terhadap Keterampilan Menggiring Bola Pada Pemain Sepak Bola - Sabila Nur Fajrin (2020)
Dribbling is a basic technique that is important in football games because players are required to run constantly carrying the ball to put the ball into the goal. Dribbling skills related to coordination, especially leg coordination, because without coordination the player will be difficult to determine the position of the ball when dribbled. The purpose of this literature review is to analyze and examine previous research conducted on the study of the correlation of coordination on dribbling skills in soccer players. This literature review method is a traditional literature review method, which is a complete, critical, and objective analysis related to the science or knowledge of a particular topic that does not have a specific method in the literature search strategy. Based on the 5 articles, shows there is a correlation of coordination on dribbling skills in soccer players. This was concluded based on the results of the analysis of the article and based on the assessment of the quality of the article which has a Q4 value on Scimago Journal & Country Rank (SJR), S4 value on SINTA (Science and Technology Index) and category B values according to Levels of Internal Validity in the Critical Appraisal method.